2017
DOI: 10.1097/sla.0000000000002419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Outcomes Between Donation After Circulatory Death and Donation After Brain Death Liver Transplantation Using the Comprehensive Complication Index

Abstract: This analysis shows a comparable complication rate during the index hospital stay for DCD and DBD LT, but the CCI increases significantly for DCD recipients in 6 months after transplantation. Reduction of biliary complications, especially ITBL, is needed to improve the outcomes for DCD grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 33 publications
8
55
1
Order By: Relevance
“…Nevertheless, graft survival at 5 years was significantly lower in DCD recipients (54.4%) compared with DBD recipients (65.6%; P = 0.02) . Similar results were recently reported by a group in the Netherlands, evaluating DCD versus DBD LT from 2001 to 2015 (n = 115 and 326, respectively) . The authors of this series reported similar patient survival but lower graft survival in the DCD group compared with the DBD group at 5 years (60% versus 75%; P = 0.002) .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Nevertheless, graft survival at 5 years was significantly lower in DCD recipients (54.4%) compared with DBD recipients (65.6%; P = 0.02) . Similar results were recently reported by a group in the Netherlands, evaluating DCD versus DBD LT from 2001 to 2015 (n = 115 and 326, respectively) . The authors of this series reported similar patient survival but lower graft survival in the DCD group compared with the DBD group at 5 years (60% versus 75%; P = 0.002) .…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were recently reported by a group in the Netherlands, evaluating DCD versus DBD LT from 2001 to 2015 (n = 115 and 326, respectively) . The authors of this series reported similar patient survival but lower graft survival in the DCD group compared with the DBD group at 5 years (60% versus 75%; P = 0.002) . Additionally, this group evaluated the CCI as a measure of the entire burden of postoperative morbidity up to 6 months after LT.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the study by Croome et al, (7) IC was defined as the presence of intrahepatic biliary strictures in the absence of hepatic artery thrombosis, which was confirmed by endoscopic retrograde cholangiopancreatography, magnetic resonance cholangiopancreatography, or percutaneous transhepatic cholangiography. (17,18) Early allograft dysfunction (EAD) was defined as described by Olthoff et al (19)…”
Section: Definitionsmentioning
confidence: 99%